Evaluation of in vitro Antifungal Activity of Xylosma prockia (Turcz.) Turcz. (Salicaceae) Leaves Against Cryptococcus spp. - Folly, Mariany L. C.; Ferreira, Gabriella F.; Salvador, Maiara R.; Sathler, Ana A.; da Silva, Guilherme F.; Santos, Joice Castelo Branco; Santos, Julliana R. A. dos; Nunes Neto, Wallace Ribeiro; Rodrigues, João Francisco Silva; Fernandes, Elizabeth Soares; da Silva, Luís Cláudio Nascimento; de Freitas, Gustavo José Cota; et al. (Frontiers in Microbiology, 2020)
Species of Cryptococcus sp. are responsible for important systemic mycosis and are estimated to cause millions of new cases annually. The available therapy is limited due to the high toxicity and the increasing rates of yeast resistance to antifungal drugs. Popularly known as “sucará”, Xylosma prockia (Turcz.) Turcz. (Salicaceae) is a native plant from Brazil with little information on its pharmacological potential. In this work, we evaluated in vitro anticryptococcal effects of the leaf ethanolic extract of X. prockia and its fractions against Cryptococcus gattii and C. neoformans. We also evaluated phenotypic alterations caused by ethyl acetate fraction (EAF) (chosen according to its biological results). The LC-MS analysis of EAF demonstrated the presence of phenolic metabolites that belong to three structural related groups as majority compounds: caffeoyl-quinic acid, coumaroyl-glucosides and caffeoyl-glucosides/deoxyhexosyl-caffeoyl glucosides derivatives. The MIC values against C. gattii and C. neoformans ranged from 8 to 64 mg/L and 0.5 to 8 mg/L, for ethanolic extract and EAF, respectively. The EAF triggered an oxidative burst and promoted lipid peroxidation. EAF also induced a reduction of ergosterol content in the pathogen cell membrane. These effects were not associated with alterations in the cell surface charge or in the thermodynamic fingerprint of the molecular interaction between EAF and the yeasts evaluated. Cytotoxic experiments with PBMC demonstrated that EAF was more selective for yeasts than PBMC. The results may provide evidence that Xylosma prockia leaf extract might indeed be a potential source of antifungal agents.